Sequence analysis of mitochondrial DNA hypervariable region i in Thai individuals - Padchanee Sangthong (2018)
© 2014 Australian Academy of Forensic Sciences. Nucleotide sequence analysis of hypervariable region I (HVRI) in human mitochondrial DNA (mtDNA) was investigated in 100 unrelated Thai individuals. A total of 85 variable sites and 423 base substitutions, which consisted of 390 nucleotide transitions and 33 nucleotide transversions were found. The following nucleotide substitutions were found: 48% at 16,223, 31% at 16,304, 30% at 16,332, and 26% at 16,129, respectively. Transition from T to C (43.7%) was the most frequent substitution. The nucleotide insertions were found at two sites with T at position 16,188 and C at position 16,194. Eighty-two haplotypes were investigated of which 72 haplotypes were unique. The most frequent haplotypes (16,108T-16,129A-16,162G-16,172C-16,304C and 16,260T-16,298C-16,355T-16,362C) were observed. From position 16,180 to 16,193, thirteen patterns of polycytosine or C-stretch were observed, whereas 68 Thai individuals were found to be similar to the references. The genetic diversity, random match probability, and discrimination power were estimated to be 0.9943, 0.0156, and 0.9844, respectively.